Comparative NMR metabolomics of the responses of A2780 human ovarian cancer cells to clinically established Pt-based drugs. Issue 33 (9th August 2022) - Ghini, Veronica; Magherini, Francesca; Massai, Lara; Messori, Luigi; Turano, Paola
Abstract : A systematic and comparative 1 H NMR metabolomics study is carried out to analyse the response of A2780 cancer cells to clinically established Pt drugs. The observed changes are referred to specific alterations of cellular processes. Abstract : Pt-Based drugs play a very important role in current cancer treatments; yet, their cellular and mechanistic aspects are not fully understood. NMR metabolomics provides a powerful tool to investigate the metabolic perturbations induced by Pt drugs in cancer cells and decipher their meaning in relation to the presumed molecular mechanisms. We have carried out a systematic and comparative 1 H NMR metabolomics study to analyze the responses of A2780 human ovarian cancer cells to the main clinically established Pt drugs, i.e., cisplatin, carboplatin and oxaliplatin. Notably, NMR analysis revealed some moderate and consistent changes in the metabolomic profiles of A2780 cells treated with the 3 Pt drugs with respect to controls, but only very small differences among them. Beyond alterations at the level of nucleic acid precursors, the observed changes highlight in all cases the induction of a significant endoplasmic reticulum stress. Owing to the clinical relevance of platinum resistance, the behavior of a cisplatin resistant A2780 cancer cell line upon cisplatin treatment was also evaluated.